2021
DOI: 10.1111/jfs.12958
|View full text |Cite
|
Sign up to set email alerts
|

Freeze–thaw enhanced stability and mechanical strength of polysaccharide‐based sodium alginate/hyaluronic acid films

Abstract: An edible polysaccharide film with high tensile strength and biodegradability was prepared by freeze-thaw treatment with sodium alginate (SA) and hyaluronic acid (HA) and cross-linking with calcium lactate. The SA/HA ratio, the calcium concentration, the number of freeze-thaw cycles, and the calcification time all have significant effects on the tensile strength of SA/HA films. An increase in tensile strength was obtained due to the reaction of 3% calcium lactate with 60% SA. Compared with the control group, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The number of crosslinked molecules forming an insoluble gel fraction is reflected by the gel content of a hydrogel, while the non-crosslinked portion of the hydrogel dissolves upon immersion in a solvent, leading to a reduction in the sample weight [ 116 ]. In addition to PVA crosslinking, freeze–thaw cycles have been demonstrated to promote the formation of intermolecular bonds in Alg [ 84 , 117 , 118 ], collagen [ 101 , 119 ] and hyaluronic acid [ 100 , 120 ]. The biohybrid hydrogel membranes were found to exhibit lower values for the gel fraction when compared to the corresponding hybrid hydrogel membranes, as expected from previous assays.…”
Section: Resultsmentioning
confidence: 99%
“…The number of crosslinked molecules forming an insoluble gel fraction is reflected by the gel content of a hydrogel, while the non-crosslinked portion of the hydrogel dissolves upon immersion in a solvent, leading to a reduction in the sample weight [ 116 ]. In addition to PVA crosslinking, freeze–thaw cycles have been demonstrated to promote the formation of intermolecular bonds in Alg [ 84 , 117 , 118 ], collagen [ 101 , 119 ] and hyaluronic acid [ 100 , 120 ]. The biohybrid hydrogel membranes were found to exhibit lower values for the gel fraction when compared to the corresponding hybrid hydrogel membranes, as expected from previous assays.…”
Section: Resultsmentioning
confidence: 99%
“…The F/T method also allows for improved stability of films. Li et al [ 115 ] developed polysaccharide-based sodium alginate (SA) and hyaluronic acid (HA) films and demonstrated that SA/HA film swelling and solubility decreased by half during the F/T period and that the material had the potential to overcome the poor water vapor barrier problems traditionally experienced with these films. Scanning electron microscopy revealed that the cross sections of the films are uniform and compact after two F/T treatments.…”
Section: Pharmaceutical Applications Of Freeze-thawmentioning
confidence: 99%
“…Additionally, OLG presence increases the antifungal drug activity. The latest scientific reports confirm that the freeze-thaw technique increases the stability and mechanical resistance of alginate-based films [ 25 ], and the effective loading of other active substances, e.g., with antioxidant properties [ 26 ].…”
Section: Alginatementioning
confidence: 99%